Yellow Card: Potential Neighborhood Impacts of a Soccer Specific Stadium Development in East Somerville. - Woods, Melissa. (2017)
Abstract: This thesis focuses on the potential economic development and environmental health impacts of a 25,000 seat soccer stadium in the Inner Belt and Brickbottom neighborhoods of East Somerville, Massachusetts. The goal of this thesis is to provide recommendations to Somerville about development in the Inner Belt and Brickbottom neighborhoods as it relates to the relocation of the New England Revolution soccer stadium. To make recommendations to Somerville, 10 planning and economic development documents were reviewed from Carson and San Jose, California; Sandy, Utah; Harrison, New Jersey; Bridgeview, Illinois; and Portland, Oregon. These stadiums were built (or majorly renovated) for MLS soccer teams and have access to public transportation. Documents were reviewed for economic development and environmental health impacts. There are many similarities between these other cities and Somerville including a need for a diversified tax base, replacing underutilized industrial sites, and creating a draw for their city. Somerville has shown that it has the capability to work with their residents on complex issues and should proceed with caution as they evaluate a mixed-use stadium development using an independent economic development impacts study and a health impact assessment.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Mary Davis.; Committee: Ann Rappaport, and Wig Zamore.; Keywords: Urban planning, and Environmental health.